Indicators of Complexity and Over-Complexification in Global Food Systems - Loring, Philip A.; Sanyal, Palash (Frontiers in Sustainable Food Systems, 2021)
Global food systems have increased in complexity significantly since the mid-twentieth century, through such innovations as mechanization, irrigation, genetic modification, and the globalization of supply chains. While complexification can be an effective problem-solving strategy, over-complexification can cause environmental degradation and lead systems to become increasingly dependent on external subsidies and vulnerable to collapse. Here, we explore a wide array of evidence of complexification and over-complexification in contemporary global food systems, drawing on data from the Food and Agriculture Organization and elsewhere. We find that food systems in developed, emerging, and least developed countries have all followed a trajectory of complexification, but that return on investments for energy and other food system inputs have significantly declined—a key indicator of over-complexification. Food systems in developed countries are further along in the process of over-complexification than least developed and emerging countries. Recent agricultural developments, specifically the introduction of genetically modified crops, have not altered this trend or improved return on investments for inputs into food systems. Similarly, emerging innovations belonging to the “digital agricultural revolution” are likewise accompanied by energy demands that may further exacerbate over-complexification. To reverse over-complexification, we discuss strategies including innovation by subtraction, agroecology, and disruptive technology.